2017
DOI: 10.1103/physrevapplied.7.064016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Control of the Polarity of BiCoO3 by Orbital Excitation as Investigated by Femtosecond Spectroscopy

Abstract: BiCoO 3 is a perovskite-type cobalt oxide with a polar structure. We investigated dynamics of its polar state by using photoexcitation with femtosecond visible and THz pulses. The intensity of the second harmonic light, caused by a polar structure without inversion symmetry, was enhanced by more than 50% by irradiating the THz pulse showing ultrafast response following the fs THz pulse. In contrast, it was suppressed by more than 60% by exciting visible light with 100fs pulse width at room temperature. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Some SC materials, especially Fe 2+ complexes are known to show the perpetual photoinduced spin state transition between the HS and LS state in several iron complexes [1], and furthermore, the detailed dynamics of SC has also recently been investigated using a femtosecond (fs) laser and/or X-ray pulses [14,15]. From this respect, we have conducted ultrafast spectroscopy on several cobalt perovskites and so far demonstrated some works concerning the photoinduced electronic change involved in the SC phenomena [16][17][18]. One example is the LSCO system [19], on which we conducted time-resolved fs reflection spectroscopy and revealed that photoirradiation with 400 nm laser pulses could realize an exotic photoexcited state that is different from the thermally induced HS state.…”
Section: Introductionmentioning
confidence: 99%
“…Some SC materials, especially Fe 2+ complexes are known to show the perpetual photoinduced spin state transition between the HS and LS state in several iron complexes [1], and furthermore, the detailed dynamics of SC has also recently been investigated using a femtosecond (fs) laser and/or X-ray pulses [14,15]. From this respect, we have conducted ultrafast spectroscopy on several cobalt perovskites and so far demonstrated some works concerning the photoinduced electronic change involved in the SC phenomena [16][17][18]. One example is the LSCO system [19], on which we conducted time-resolved fs reflection spectroscopy and revealed that photoirradiation with 400 nm laser pulses could realize an exotic photoexcited state that is different from the thermally induced HS state.…”
Section: Introductionmentioning
confidence: 99%
“…First, we discuss the results of terahertz-pulse-pump SHG-probe measurements (Fig. 1b ), which detect the dynamics of polarization changes by an electric-field pulse 16 20 . Before the measurements, a static electric field F s of ±30 kV/cm (| F s | > F c ) is applied along the c axis to align the polarization and then it is released.…”
Section: Resultsmentioning
confidence: 99%
“…The original proposal to switch the polarization by resonant excitation of the ferroelectric mode [11][12][13] has not yet been fully realized experimentally [14][15][16][17]. It was also shown that optical pumping with excitation of the electronic subsystem [18][19][20][21] leads only to a temporary decrease in polarization [22][23][24][25]. Following the rapid development and achievements of nonlinear phononics [26][27][28][29], it was proposed to pump the IR-active optical phonon mode, which is nonlinearly coupled with the ferroelectric soft mode [30].…”
mentioning
confidence: 99%
“…In experiments with optical pumping [23][24][25], the penetration depth of the pump pulse varies from about 3 nm [25] upto 100 nm [24], depending on the crystal used. In this case, the depolarization factor should already be very small, and the depolarizing field is strongly reduced.…”
mentioning
confidence: 99%